2018
DOI: 10.1371/journal.pone.0191560
|View full text |Cite
|
Sign up to set email alerts
|

Association between TERT rs2853669 polymorphism and cancer risk: A meta-analysis of 9,157 cases and 11,073 controls

Abstract: BackgroundIt has been reported that the functional telomerase reverse transcriptase (TERT) rs2853669 polymorphism might contribute to different types of human cancer. However, the association of this mutation with cancer remains controversial. Here, we conducted a meta-analysis to characterize this relationship.Materials and methods/Main resultsA systematic search of studies on the association of TERT rs2853669 polymorphism with all types of cancer was conducted in PubMed, Embase and Cochrane Library. The summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…SNP rs2853669 has been frequently detected in some malignant tumors such as hepatocellular carcinomas, pulmonary carcinomas, glioblastomas, acute myeloid leukemia, and prostatic carcinomas . Rs2853669 is related to the risk of lung cancer in Asian countries . Ko et al reported that rs2853669 enhanced E2F1 binding and C228T increased ETS2 binding at the TERT promoter, and the combination enhanced TERT promoter methylation and increased TERT promoter activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SNP rs2853669 has been frequently detected in some malignant tumors such as hepatocellular carcinomas, pulmonary carcinomas, glioblastomas, acute myeloid leukemia, and prostatic carcinomas . Rs2853669 is related to the risk of lung cancer in Asian countries . Ko et al reported that rs2853669 enhanced E2F1 binding and C228T increased ETS2 binding at the TERT promoter, and the combination enhanced TERT promoter methylation and increased TERT promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to 1000 genome data, the allelic C frequency of this SNP was 24.5% in the population of Tokyo. Liu et al conducted a meta‐analysis to clarify the association between the TERT rs2853669 polymorphism and cancer risk, and the frequencies of CC, CT and TT were 10.4% (207), 43.1% (859), and 46.5% (926) of 1992 Asians in the control group, respectively. The allelic C frequency in the Asian population was found to be 32.0% (1273 of 3984 genes) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between TPM and TERT gene expression has shown significantly higher levels of mRNA expression in mesothelioma indicating that genetic alterations of the TERT promoter are a mechanism of TERT mRNA upregulation in mesothelioma 94 . Recent results of a meta-analysis suggested that the TERT rs2853669 polymorphism is associated with a significantly increased risk of cancer, particularly lung cancer; in Asian populations 95 , the TERT rs2853669 T>C polymorphism (SNP), located upstream of the TERT promoter region, has been shown to affect telomerase activity and TL.…”
Section: Barcelona Respiratory Networkmentioning
confidence: 99%